THE ROLE OF SOCIAL MEDIA AND MOBILE DEVICE ON E-COMMERCE IN MICRO SMALL MEDIUM ENTERPRISE IN MANADO - Turangan, Christian .; Lapian, S.L.H.V Joyce; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Â Abstract: The Electronic commerce or E-commerce is one form of development in the field of technology, it looks promising, e-commerce makes economic actors especially micro small and medium enterprises to compete and start utilize the technology, many micro small and medium enterprises that implement e-commerce systems in running their business, but from the number of transactions e-commerce in Indonesia still shows the number of transactions that are classified as low. apart from e-commerce, social media and mobile devices is also a form of world development, it used to communicate and many others, MSMEs involving social media and mobile devices in running a business, From the data there are two objectives to be achieved is what is the role of social media and mobile devices on e-commerce in MSMEs, and to ensure that the intended objectives can be achieved, qualitative methods used as a research method, as well as conducting in-depth interviews. From the interview found that the results of social media into the media in promoting and also interact with buyers and mobile devices into a tool to carry out payment transactions. And recommendations obtained after this research is MSME should maximize the use of social media and mobile devices.Keywords: e-commerce, micro small medium enterprise, social media, mobile device